Modulation of left ventricular hypertrophy in spontaneously hypertensive rats by acetylcholinesterase and ACE inhibitors: physiological, biochemical, and proteomic studies - Hejnova, Lucie; Drastichova, Zdenka; Boroš, Almos; Hrdlicka, Jaroslav; Behuliak, Michal; Neckar, Jan; Zicha, Josef; Novotny, Jiri (Frontiers in cardiovascular medicine, 2024)
BACKGROUND: The consequences at the molecular level and the mechanisms involved in a possible cardioprotective effect of antihypertensive treatment are not yet fully understood. Here, the efficacy of pyridostigmine (PYR) and trandolapril (TRA) as antihypertensive and antihypertrophic agents was investigated and compared in hypertensive SHR and normotensive WKY rats. In parallel, we investigated the effects of these drugs on myocardial β-adrenergic and cholinergic signaling pathways and protein expression profiles. METHODS: Age-matched male SHR and WKY rats were chronically (8 weeks) treated with PYR or TRA in drinking water. Blood pressure (BP) and heart rate (HR) were monitored telemetrically prior to tissue sampling for biochemical analysis. Baroreceptor reflex sensitivity (BRS) and methylatropine HR response as a measure of vagal tone were evaluated in separate groups of animals. RESULTS: PYR slightly lowered BP and HR in SHR rats during the dark phase of the day, while TRA effectively reduced BP during the light and dark phases without affecting HR. PYR enhanced BRS and improved vagal tone. There were no significant alterations in myocardial β-adrenergic and cholinergic signaling, with the exception of decreased forskolin-stimulated adenylyl cyclase (AC) activity in SHR rats, which was restored by TRA. Proteomic analysis revealed numerous differences induced by both treatments. Notable were changes in TGFβ-related signaling pathways as well as proteins involved in modifying hemodynamic parameters and cardiac hypertrophy. CONCLUSIONS: PYR is able to slightly decrease BP and HR in SHR rats but effectively increase BRS through vagal potentiation. The specific differences in protein expression profiles in rat myocardium induced by treatment with PYR and TRA reflect different mechanisms of action of these two agents at the molecular level.
Keywords: pyridostigmine; SHR and WKY rats; myocardial proteome; trandolapril; hypertension; cholinergic signaling; acetylcholinesterase